Biofilms retard the desorption of benzo(a)pyrene from polyethylene pellets in the marine environment - Hao, Xiaohan; Zhang, Ying; Sun, Yueling; Liu, Hongtao; Zhang, Xiaohan; Li, Xiaofeng; Ma, Yongzheng; Niu, Zhiguang (Marine pollution bulletin, 2023)
Microplastics are emerging as vectors for the transport hydrophobic organic compounds (HOCs) in aquatic environments, however, their impact is poorly understood due to the lack of field studies. In this study, the pristine and benzo(a)pyrene (B[a]P) adsorbed polyethylene (PE) pellets were placed at Haihe Estuary (Tianjin, China) for 80 days to investigate desorption behavior. Combining laboratory and in situ experiments, this study firstly verified that the intra-particle diffusion was the rate-limiting step for the desorption process of B[a]P from PE microplastics under different environmental conditions. By hindering the desorption and modifying MPs surface, biofilm might play a key role in desorption process, leading to the apparent hysteresis of the field desorption process at our time scale. Potential degradation of the polymer and B[a]P by biofilms, however, would support continuing desorption. The study explored the interaction of biofilm and MPs-contaminants mixture and its implications for the environmental fate of HOCs. [Display omitted] •The desorption characteristic of B[a]P from PE in field environment was probed.•The interaction of biofilm and MPs-contaminants mixture was explored.•Biofilms were the primary factor influencing the desorption of B[a]P from PE.•Hindering and degradation effects of biofilm led to the hysteresis of desorption.